2020
DOI: 10.1021/acs.chemmater.0c00196
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of the Nonlinear Optical Response in a Tin Iodate Fluoride Sn(IO3)2F2

Abstract: A new tin iodate fluoride, Sn­(IO3)2F2, was meticulously designed based on Sn­(IO3)4 with an intriguing chemical tailoring transformation from the centrosymmetric to noncentrosymmetric structure. Sn­(IO3)2F2 crystallizes in polar space group P21 and features an one-dimensional chain constructed by IO3 and SnO4F2. It has an enlarged band gap (4.08 eV) compared to the Sn­(IO3)4 (3.96 eV) because of the introduction of strong electronegative F–. Also, powder second-harmonic generation (SHG) measurements revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 52 publications
4
64
0
Order By: Relevance
“…The lack of spatial inversion symmetry can stabilize asymmetric exchange interactions in systems with unpaired electrons, giving rise to novel physical phenomena such as multiferroics and topological spin textures [1][2][3][4][5][6]. However, engineering noncentrosymmetric (NCS) polar crystal structures for magnetic materials remains difficult, owing to a combination of several factors such as dipole-dipole interaction, steric effect, and thermodynamic effects, which often yield centrosymmetric lattices in transition metal complexes [7][8][9][10]. Polar asymmetric anions with stereo-active lone-pair electrons such as (SeO 3 ) 2− and (IO 3 ) − trigonal pyramids provide avenues for accessing NCS polar structures, facilitated by the second-order Jahn-Teller distortion [6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of spatial inversion symmetry can stabilize asymmetric exchange interactions in systems with unpaired electrons, giving rise to novel physical phenomena such as multiferroics and topological spin textures [1][2][3][4][5][6]. However, engineering noncentrosymmetric (NCS) polar crystal structures for magnetic materials remains difficult, owing to a combination of several factors such as dipole-dipole interaction, steric effect, and thermodynamic effects, which often yield centrosymmetric lattices in transition metal complexes [7][8][9][10]. Polar asymmetric anions with stereo-active lone-pair electrons such as (SeO 3 ) 2− and (IO 3 ) − trigonal pyramids provide avenues for accessing NCS polar structures, facilitated by the second-order Jahn-Teller distortion [6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For the design of NCS structures, a series of strategies have been proposed, for example, introducing the p-conjugated anion groups or the distorted polyhedra with the second-order Jahn-taller (SOJT) effect cations, namely, d 0 transition metals (Ti 4+ , Nb 5+ , or W 6+ ) and cations with nonbonded electron pairs (Se 4+ , Te 4+ , or Sb 3+ ), etc. [19][20][21][22][23][24][25] Among them, the structure-directing properties of earlytransition-metal (ETM) oxide-fluoride anions caught particular attention. [26][27][28][29][30][31][32][33][34] For one thing, the local site symmetry of the ETM cation is changed from centrosymmetric to noncentrosymmetric and polar as a result of the SOJT effect, which will favor the formation of NCS structures.…”
mentioning
confidence: 99%
“…For the explored multiple anionic systems, the most ones include borate halides, [9] iodate halides, [10,11] vanadate iodates, [12,13] chalcogenide halides, [14][15][16] mixed-anion borates, [17,18] and chalcogenide borates. [19,20] From these systems' success, it can be concluded that it is a tendency to explore new multiple anionic materials for new materials' growth point.…”
Section: Introductionmentioning
confidence: 99%